Secure Authentication in Vehicular Networks: Integrating Zero-Knowledge Protocols with RSS Key Generation - Kriswantoro, M. Cahyo; Handoyo, Eko; Sa Yu Zakka, Mutsna (Universitas Dr. Soetomo, 2025)
Zero Knowledge Authentication protocol is a cryptographic method used to identify users through interactive communications without exposing confidential. The identification scheme is an example of a real-world application of the Zero-Knowledge protocol, which provides a mechanism for actors in possession of a secret key to verify their identity using the corresponding public key. Several prominent identification schemes have been proposed in the literature, including the Feige-Fiat-Shamir (FFS), Guillou-Quisquater (GQ), and Schnorr protocols. In conjunction with these schemes, mechanisms for key generation and key updates have been developed to enhance privacy in zero-knowledge cloud-based file storage systems. To ensure data integrity within cloud environments, the Shacham-Waters auditing protocol has been employed. The FFS identification scheme, in particular, utilizes a public-private key pair in a parallel verification structure. To improve computational efficiency, this scheme has been enhanced by incorporating parallel constructions. Researchers utilize the Zero-Knowledge Authentication Feige-Fiat-Shamir protocol by combining the key generator obtained from Received Signal Strength (RSS) in vehicle communications, thereby replacing the channel in the Feige-Fiat-Shamir protocol with the key generator derived from RSS. The existing combination combines stages 1 and 4 in FFS. The change is that the channel sent is replaced with a key generator obtained from the RSS key generator. The results of this study are expected to serve as a reference for the implementation of vehicle communication technology, which is anticipated to experience rapid growth in the future.